ASSESSING THE CAPACITY OF COUNTY HEALTH DEPARTMENTS IN KENYA USING THE WORLD HEALTH ORGANIZATION'S HEALTH SYSTEMS FRAMEWORK: IMPLICATIONS FOR SERVICE DELIVERY AND OUTCOMES - Vincent R. OKUNGU (Rojan GÜMÜŞ, 2019)
The study used the county institutional capacity assessment tool (CICAT) to assess the capacities of selected county health departments (CHDs) along the World Health Organization (WHO) health systems framework that is organized around the six building blocks. The aim was to determine the current status of the six health system building blocks in Kenya's county health departments. The article emanates from data collected for a technical report on county institutional capacity assessment. Data were analysed using Microsoft Excel spreadsheet and thematic analysis. The overall performance of the counties was 54% indicating average capacity. The performance scores were: leadership and governance (39%), human resources for health (44%), health information systems (66%), medical products and technologies (50%), health system financing (50%), and service delivery (71%). There was no statistically significant difference in the overall performance of the counties (p= 0.892). The key issues in some of the worst performing building blocks included poor work-planning and lack of transparency in budgeting and expenditure, low funding and irregular disbursements of health budgets, lack of key policies, e.g. workforce strategy and commodity supply chain. In conclusion, the study proved that the CICAT is useful for assessing the process of strengthening health systems in Kenyan counties.